A series of luminescent Cu(i) complexes based on the diphosphine ligand and diimine ligand: weak intermolecular interactions, terahertz spectroscopy and photoproperties. Issue 47 (10th November 2021) - Li, Zi-Xi; Kuang, Xiao-Nan; Wang, Guo; Zhu, Ning; Sun, Zhen-Zhou; Han, Hong-Liang; Yang, Yu-Ping; Li, Zhong-Feng; Xin, Xiu-Lan; Jin, Qiong-Hua; Ren, Zhi-Gang
Abstract : Counter-ions can regulate the luminescence of complexes by changing the weak intermolecular interactions, which can be observed by THz spectroscopy. Abstract : Five novel mononuclear [Cu(Bphen)(bdppmapy)]X complexes showing photoluminescence were synthesized. The same diphosphine ligand and diimine ligand and different Cu(i ) salts were used in the one-pot synthesis of complexes 1–5 . These complexes are listed as follows: [Cu(Bphen)(bdppmapy)]CF3 SO3 (1 ), [Cu(Bphen)(bdppmapy)]BF4 ·0.268CH3 OH (2 ), [Cu(Bphen)(bdppmapy)]ClO4 (3 ), [Cu(Bphen)(bdppmapy)]I·CH3 OH (4 ) and [Cu(Bphen)(bdppmapy)]Br·2CH3 OH (5 ) (Bphen = 4, 7-diphenyl-1, 10-phenanthroline, bdppmapy = N, N -bis((diphenylphosphino)methyl)-2-pyridinamine). IR, NMR, elemental analysis, single-crystal X-ray diffraction analysis, UV-vis, fluorescence spectroscopy and terahertz time-domain absorption spectroscopy (THz-TDS) were used to characterize 1–5 . Their crystal structures have been elucidated by X-ray crystallography and their photophysical properties have been investigated in detail. These five complexes have a similar coordination center, while their space stacked structures are different, from a 0D dimeric structure to a 3D supramolecular structure. Photophysical studies and density functional theory calculations (DFT) show that the luminescence properties of these five complexes are mainly ascribed to metal-to-ligand charge transfer (MLCT). Among these five complexes, 1 emits luminescence with the highest quantum yield of 36.96% and a lifetime of 11.90 μs at ambient temperature. Different counter-anions lead to the distinction of QYs, maybe due to the influence of weak forces. Terahertz time-domain absorption spectroscopy was used to characterize these ligands and complexes in the range of 0.2–2.4 THz.